Harassment, Corruption and Economic Policy - Sugata Marjit; Vivekananda Mukherjee; Arijit Mukherjee (Center for Economic Studies and ifo Institute (CESifo), 1999)
This paper introduces harassment in a model of bribery and corruption. We characterize the harassment equilibrium and show that taxpayers with all possible levels of income participate in such an equilibrium. Harassment has a regressive bias. Harassment cost as such may not affect tax revenue. However, when the decision to file tax-returns is endogenized, harassment cost can affect the filing pattern and hence the revenue collection. We study the nature of the equilibrium under imperfect information when different types of taxpayers and different types of auditors are introduced in the system.
Keywords: 330; Corruption; Harassment; Filing